Comparative Cost And Return Analysis Of Eight Major Vegetables In Char Land Ecosystem Of Bangladesh (SAARC Journal of Agriculture, 2024)
Bangladesh has tremendous opportunities to harness the potential of the agriculture sector like in vegetable sector which is contributing to our export sector too. Thus, the main focus of this study is to assess the financial profitability of selected eight major vegetables. The cost and return scenario of eight major vegetables that most of the farmers cultivate in the char land area such as brinjal, tomato, chili, bitter gourd, pumpkin, okra, bottle gourd, and amaranth were done for the study. Study areas were chosen in the districts of Mymensingh, Jamalpur, and Sherpur in Bangladesh following a simple random sampling procedure where 240 farmers were surveyed. The results show that the highest and lowest net return found for bottle gourd and okra, were Tk. 195,118 ha-1 and Tk. 32,894 ha-1, respectively. Further, in terms of gross return, bottle gourd production is the most profitable but in terms of net return both the brinjal and tomato are in the same position. The benefit-cost ratio (BCR) was the highest (1.98) for bottle gourd followed by tomato (1.96). Among the cost items, labor cost occupies more than half of the total cost which proves that vegetable production is labor-intensive cultivation. The ranking by variable and total cost revealed that farmers frequently choose the lowest-cost production method and the okra is the most preferred product in that method. However, a ranking of the probability of all vegetables was also done. This ranking will help farmers to take their decision according to their resource availability.SAARC J. Agric., 22(1): 223-234 (2024)